Evaluation of a Primary Treatment Unit for the Cooling Water of a Nuclear Power Plant (Journal of Nuclear Technology in Applied Science, 2018)
It is essential to have an effective treatment program and controlmethodology for a nuclear power plant cooling water system. As the ac- cumulation and growth of cooling water deposits reduce the overall heat transfer coefficient and have an adverse effect on the operation of equip-ments, plant availability, production, and maintenance cost. The studyaims at evaluationof using a primary treatment unit debris filter as a con-trolling of fouling formation, in a nuclear power plant located in coastal area. Selecting Sedi kerir, and Sidi Abdelrahman cooling water channel for the proposed nuclear power plant. Samples of the two selected sites had been taken and some physicochemical and biological parameters were analyzed such as (pH, total alkalinity, total dissolved solids, suspended solids, temperature and total count of microalgae). A mathematical modelhas been used also in order to help in evaluation of the suggested pretreat-ment unit. The results has showed that sea water temperature used at the two selected sites (Sidi kerir, and Sidi Abdelrahman below 1250F that mean low fouling factor, also the measured physicochemical and biologi-cal parameter concentrations at the proposed two selected sites increase the probability of fouling formation at these sites. As a using of suggested debris filter pretreatment unit for cooling water at the two selected sites,will help in decreasing the probability of fouling formation at these site.
Keywords: Cooling Water; Bio- fouling; Debris Filter; volume and specific